From single market to economic union essays in memory of John A. Usher - Nic Shuibhne, Niamh; Gormley, Laurence W. (Laurence William), 1953-; Usher, John A. (John Anthony), 1945-2008. (Oxford : Oxford University Press, 2012)
Leading figures in European law discuss the evolution and regulation of the EU as an economic union, in tribute to the scholarship of the late Professor John Usher, one of the pioneers of the field.
Description based on online resource; title from home page (viewed on July 12, 2012).
Includes bibliographical references and index.
Keywords: European Union; European Union countries -- Economic integration; Monetary unions -- Law and legislation -- European Union countries